The present knowledge on soil pests and pathogens in Uganda - Sekamatte, M. B.; Okwakol, M. J. N. (African Journal of Ecology, 2007)
To develop an inventory of the present knowledge about soil-borne pests (insects, fungi, nematodes and bacteria) in Uganda, we review in this paper, aspects of their diversity, abundance, distribution in agro-ecosystems control approaches as well as their role in sustainable land management. Knowledge gaps about the soil pests and short falls in human resource capacity are identified as possible factors affecting the development of appropriate management packages for the soil pests. Priority research areas and capacity building needs are suggested.
Keywords: Knowledge; Pathogens; Soil pests; Uganda